A VAN DIJK APPROACH TO BUGINESE FOLKLORE “Tau Sakbarak E” (Socio-Cultural and Linguistic Aspects) - Muhammad Syukri; Fatimah Hidayahni Amin; St. Rahmaniah Bahrun; Heriyanti (JLE: Journal of Literate of English Education Study Program, 2022)
The purpose of this research is to explore aspects of discourse analysis through Van Dijk's approach to folklore. This folklore contains many educational values, ethics, norms as well as socio-cultural aspects. For the analysis of discourse on folklore, the Van Dijk model, which emphasizes elements of critical discourse, was used (Critical Discourse Analysis). This research is library research by using the naturalistic approach with Van Dijk model analysis. The result of this research was the aspects analyzed of macrostructure and microstructure. The macro structure is thematic and schematic. The element analyzed the essence of the theme of the discourse. That is morality (admirable nature) or “good morality”. In the micro structure analyzed aspects of semantic, syntax, stylictic, and rethoric. In semantic aspect analyzed conceptual meaning, connotative meaning, social meaning, affective meaning, reflective meaning, collocative meaning and thematic meaning.